G protein-coupled estrogen receptor (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database - Filardo, Edward; Neubig, Richard; Prossnitz, Eric R. (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The G protein-coupled estrogen receptor (GPER, nomenclature as agreed by the NC-IUPHAR Subcommittee on the G protein-coupled estrogen receptor [24]) was identified following observations of estrogen-evoked cyclic AMP signalling in breast cancer cells [2], which mirrored the differential expression of an orphan 7-transmembrane receptor GPR30 [5]. There are observations of both cell-surface and intracellular expression of the GPER receptor [27, 32]. Selective agonist/ antagonists for GPER have been characterized [24]. Antagonists of the nuclear estrogen receptor, such as fulvestrant [10], tamoxifen [27, 32] and raloxifene [23], as well as the flavonoid 'phytoestrogens' genistein and quercetin [16], are agonists of GPER. A complete review of GPER pharmacology has been recently published [24]. The roles of GPER in physiological systems throughout the body (cardiovascular, metabolic, endocrine, immune, reproductive) and in cancer have also been reviewed [24, 25, 18, 15, 8].